PENERAPAN SISTEM PENDIDIKAN DAN PENGAJARAN KULLIYYATU-L- MU’ALLIMIN AL- ISLAMIYYAH DALAM PEMBENTUKAN AKHLAQUL KARIMAH TERHADAP SISWA MTS-SMA AR-RIDHO SENTUL - Siddiq, Anhar Rizqonnur; Ikhtiono, Gunawan; Kamalludin (Inspiratif Pendidikan, 2023)
Education and teaching are conscious and planned efforts to create an atmosphere of learning and the learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and skills needed by themselves, society, the nation and the state. . Morals are human behavior, which can be of good value (noble) or vice versa of bad value (despicable). The application of the kulliyyatu-l-mu’allimin al-islamiyyah education and teaching system at MTs-SMA Ar-Ridho Sentul has the aim of being able to produce pious and multi-talented cadres of community leaders in every field. Based on the results of observations, the researcher wanted to know and describe the planning, implementation, evaluation of the existing education and teaching systems. Therefore this study uses a qualitative approach with case study methods for collection techniques, namely by observation, interviews, and documentation. Then to check and check data from various data collection techniques and data sources using data triangulation. The result of this research is planning the implementation of the system is not only planning to carry out teaching and learning activities in the classroom, but also activities outside the classroom including the process of implementing the education and teaching system. The implementation is by exemplary methods (uswatun hasanah), taking lessons (ibrah), advice (mauidzah), and methods of training and habituation in everyday life. As well as evaluation in its application is divided into 2 types, namely evaluation for all male students and also evaluation for all teaching asatidz.